PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW TERHADAP MATA PELAJARAN AKIDAH AKHLAK DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK DI MTS AL MUSTAQIM PAREPARE - Diza Jusriani; Ibrohim Muchlis (AL - IBRAH, 2023)
This research is motivated by the lack of variation in Islamic Religious Education learning, particularly in the subject of Aqidah Akhlaq, especially in the teaching methods applied by teachers. Many students are less focused on teacher explanations, often engaging in activities outside of learning, such as talking to classmates, and some even become sleepy during the teaching and learning process. The purpose of this study is to assess the influence of using the Jigsaw cooperative learning model on the interest of students in the Aqidah Akhlaq subject in grade VIII at MTS Al-Mustqim Parepare. This research is quantitative with an experimental design. The study aims to implement innovative learning that can enhance students' enthusiasm and learning outcomes. One proposed alternative is through the application of ice-breaking games, with the hope that students will be more enthusiastic about learning and understand the material taught by the teacher. The research subjects involve 32 students in grade VIII at MTS Al-Mustqim Parepare. Class VIII A is designated as the experimental class, where the Jigsaw Cooperative Learning Model is implemented, and for class VIII B is designated as the control class using conventional methods. Data analysis is carried out by testing normality using the Kolmogorov-Smirnov and Shapiro-Wilk formulas, homogeneity tests, and then hypothesis testing using the independent sample t-test. From the research results and data analysis conducted, there is an influence of the Jigsaw Cooperative Learning Model on the improvement of students' learning interest.